Whither compassionate leadership? A systematic review - Ramachandran, Sunder; Balasubramanian, Sreejith; James, Wayne Fabian; Al Masaeid, Turki (Management review quarterly, 2024)
Recent disastrous events, such as the COVID-19 pandemic, has amplified the appeal for compassionate leadership in organizations and is viewed as the need of the hour. While compassion is a timeless concept, there appears to be a lack of clarity around the idea of compassionate leadership, and the current understanding appears limited, fragmented, and scattered across the literature. This integrative systematic review of 41 articles during the last 20 years (2002–2021) conceptualizes six critical dimensions of compassionate leadership, namely: empathy; openness and communication; physical, mental health and well-being; inclusiveness; integrity; respect and dignity. These findings enhance our understanding of how organizational leaders can effectively incorporate the dimensions to become compassionate leaders. The review examines how compassionate leadership is defined and understood in the literature, and a contribution in the form of a definition for compassionate leadership is offered. Finally, gaps in the literature are highlighted, offering avenues for future research, along with implications for research, theory, and practice.